Strategi Meningkatkan Keterampilan Bahasa Produktif Dalam Konteks Berbicara dan Menulis Sebagai Landasan Awal Pembelajaran Menjadi Kunci Kesuksesan - Sihombing, Agni Lorensia; Azizah, Nurul; Barus, Einjelia Sovany; Nisa, Khoirun; Romadhon, Muhammad Fadhil; Ananta, Zaskia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Productive Language Skills, Including Speaking And Writing, Are Important Aspects Of Language Learning. This Study Aims To Identify Strategies That Can Improve Speaking And Writing Skills. The Main Focus Is That The Strategies Can Be Applied Efficiently, And Can Be Done At Any Time. The Research Method Used Is An Observational Study Based On Questionnaire Data Distributed To Students, And Data Collected To Obtain A Comprehensive Picture Of The Best Practices And Strategies In An Effort To Improve Productive Language Skills In The Scope Of Speaking And Writing As The Key To Success.